Structure of the polypeptide crotamine from the Brazilian rattlesnake Crotalus durissus terrificus. (8th October 2013) - Coronado, Monika A.; Gabdulkhakov, Azat; Georgieva, Dessislava; Sankaran, Banumathi; Murakami, Mario T.; Arni, Raghuvir K.; Betzel, Christian
<x xml:space="preserve">Abstract</x> The crystal structure of the myotoxic, cell‐penetrating, basic polypeptide crotamine isolated from the venom of Crotalus durissus terrificus has been determined by single‐wavelength anomalous dispersion techniques and refined at 1.7 Å resolution. The structure reveals distinct cationic and hydrophobic surface regions that are located on opposite sides of the molecule. This surface‐charge distribution indicates its possible mode of interaction with negatively charged phospholipids and other molecular targets to account for its diverse pharmacological activities. Although the sequence identity between crotamine and human β‐defensins is low, the three‐dimensional structures of these functionally related peptides are similar. Since crotamine is a leading member of a large family of myotoxic peptides, its structure will provide a basis for the design of novel cell‐penetrating molecules.